Implementation of Enforcement of the Integrity of Ad Hoc Election Organizers in the 2020 Sleman Regent and Deputy Regent Elections - Trapsi Haryadi; Ridho Al-Hamdi; Suswanta Suswanta (Political Science Program, Universitas Negeri Semarang, 2022)
The integrity of the election administration and the integrity of the election organizers are important matters in the implementation of the general election. This paper aims to explore the enforcement of the integrity of the Ad Hoc Election organizers, especially at the sub-district level, namely the PPK (Sub-district Organizing Committee) in the implementation of the 2020 Sleman Regent and Deputy Regent Elections (Election). What are the efforts made by the KPU of Sleman Regency to enforce the integrity of the Ad Hoc election organizers. This research method uses the mix-method method (quantitative and descriptive qualitative). The findings of this study are, first, that there were no violations of the code of ethics, especially the integrity of the PPK during the implementation of the election stage. Second, the Sleman Regency KPU made several efforts to maintain the integrity of the PPK. Third, the integrity of the PPK is one of the factors that boost the public participation rate, which has increased from the 2015 election. Fourth, the PPK recruitment process has an important role in getting the PPK with integrity. The policy recommendation in this study is the need for sustainable political/voter education, and the results of this political/voter education can be used as raw materials in the PPK recruitment process.